Sport injuries as the main cause of sport career termination among Finnish top-level athletes - Ristolainen, L.; Kettunen, J. A.; Kujala, U. M.; Heinonen, A. (European Journal of Sport Science, 2012)
Injuries are common among athletes, and are sometimes so severe that they affect an athlete's career in sport. As studies on sport career termination are few, we conducted a study to investigate the role of injuries as a reason for ending a sport career. The study group consisted of 574 male and female top-level cross-country skiers, swimmers, long-distance runners and soccer players who responded to a retrospective postal questionnaire in 2006. Twenty-seven athletes (4.9%, 27/548) reported ending their sport career because of injury. A follow-up interview was conducted by telephone in 2007 (n=20 volunteered to be interviewed) to confirm sport career termination and the reasons for this. Fifteen of the interviewed athletes terminated and five continued their sport on the same level as earlier. Female athletes (12/15) terminated their sport career more frequently than male athletes (3/15). Athletes who reported terminating their sport career because of injury were on average two and a half years older (24.1 years vs. 21.6 years, P=0.006) than athletes who continued the sport. All the swimmers (n=5) who were interviewed terminated their career because of a shoulder injury. All the soccer players who ended their career (n=4) were female and had a severe knee injury, such as anterior cruciate ligament injury. Most of the athletes who terminated their sport career (70.4%, 19/27) reported that the injury caused them mild or moderate permanent disability. We found that sports injuries play a significant role in terminating a career in sport, and in some sports events injuries may commonly be the main reason for sport career termination. Injury prevention and adequate treatment and rehabilitation of injuries are thus essential to avoid the long-term consequences of severe sport injuries.